ANALYSIS OF LAVENDER AROMATHERAPY APPLICATION TO REDUCE BLOOD PRESSURE IN PATIENTS WITH HYPERTENSION: A CASE STUDY - Sapeni, Muhammad Al-Amin R.; asriana, Hasriana; Anwar, Irawati; Yunus, Suwardha; Iwan, Iwan; Taniguch, Toshiyo; Lillehei, Angela Smith (PT.Mantaya Idea Batara, 2025)
Introduction: Hypertension is defined as a condition in which an individual has a systolic blood pressure ? 140 mmHg and a diastolic blood pressure ? 90 mmHg. Systolic blood pressure is the main measure used to diagnose hypertension. Hypertension is often referred to as a